2021
DOI: 10.18488/journal.31.2021.82.127.135
|View full text |Cite
|
Sign up to set email alerts
|

The Antecedent of Intention to Visit Halal Tourism Areas Using the Theory of Planned Behavior: The Moderating Effect of Religiosity

Abstract: Halal tourism has a significant current market share. The increasing number of tourists from Muslim countries is a consideration for many areas to change their marketing strategies. In various works of literature, religiosity plays a role in consumer behavior. In this study, religiosity becomes a mediating variable from the subjective norm, attitude, and perceived behavioral control (PBC) to the intention to visit a halal tourism area. This study modifies the Theory of Planned Behavior (TPB), intending to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…In addition, consumer attitudes will determine consumer intentions to buy a product or service (Davis et al, 1989). The results of a similar study also state that attitude has a positive effect and service (Julina et al, 2021) dan Rahmawati et al, (2021) (Jehane et al, 2019) (Muslima et al, 2020 show that attitude has a positive and significant correlation to the behavior of a person's intentions at halal tourist destinations.…”
Section: Previous Studiesmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, consumer attitudes will determine consumer intentions to buy a product or service (Davis et al, 1989). The results of a similar study also state that attitude has a positive effect and service (Julina et al, 2021) dan Rahmawati et al, (2021) (Jehane et al, 2019) (Muslima et al, 2020 show that attitude has a positive and significant correlation to the behavior of a person's intentions at halal tourist destinations.…”
Section: Previous Studiesmentioning
confidence: 81%
“…Thus, subjective norms are closely related to the norms that exist around the individual, so a shift in the perspective of people around the individual becomes important. Previous research conducted by Nugroho et al (2018), and Saifudin & Puspita (2020) (Julina et al, 2021) (Derizal et al, 2023 proved that subjective norms have a positive and significant influence on a person's behavioral intention.…”
Section: Previous Studiesmentioning
confidence: 92%
“…Using a sample of 100 Malaysians, Ramadhani et al (2020) revealed how subjective norms had a substantial impact on the intention to revisit halal Halal tourism and Muslim diaspora intention destinations. Further, Julina et al (2021) found that subjective norms and attitude have positively impacted on tourists' intention to visit a halal tourism destination. Their finding showed that intention is a key variable within the tourism literature, as it is a significant factor that explains a tourist's willingness to visit a destination or not.…”
Section: Hypotheses Development Halal Attitude (Ha)mentioning
confidence: 98%
“…Their finding showed that intention is a key variable within the tourism literature, as it is a significant factor that explains a tourist's willingness to visit a destination or not. From the tourism literature perspective, the belief about whether tourists like or dislike a destination will significantly affect the willingness to recommend or not recommend such a destination to other tourists (Elseidi, 2018;Julina et al, 2021). However, testing the extent to which HSN impacts on tourists' intention to recommend remains a missing link in halal tourism literature from a non-Islamic diasporic tourists' perspective.…”
Section: Hypotheses Development Halal Attitude (Ha)mentioning
confidence: 99%
See 1 more Smart Citation